FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN BPJS PADA PELAYANAN KESEHATAN IBU HAMIL DI WILAYAH KERJA PUSKESMAS CIPUTAT TIMUR - Suci Makrifah, (2023)
Using BPJS In health services for pregnant women plays a vital role in reducing the risk of complications for pregnant women, childbirth, and postpartum mothers. This study aimed to determine the relationship between income, knowledge, health services received, husband support, and health worker support using BPJS in pregnant women's health services in the East Ciputat Health Center work area. The study used a cross-sectional design with a Simple Random Sampling sampling technique and was conducted on 109 respondents. Univariate analysis showed that the majority of respondents were mothers with age not at risk (90.8%), a secondary education level (78.9%), employment status did not work 78.9%, 62.4% had low income, had good knowledge (45.9%), health services provided using BPJS were good (78%), husband support was good (88.1%), and officer support was good (54.1%). The results of the chi-square test showed that there is a relationship between income (p-value 0.000), knowledge (p-value 0.010), services received (0.000), husband support (p-value 0.017), and health worker support (p-value 0.002) with the use of BPJS.in conclusion, there is a relationship between income, knowledge, health services received, husband support, and health worker support with the use of BPJS in pregnant women's health services. The public can seek information directly from the Health Center about the BPJS service program and does not need to hesitate to utilize health services at the Public Health Center.